Utilization of Historical Site Media by Teachers in Building Student Character in Junior and Senior High Schools in the Central Amanuban Sub-District - Taneo, Malkisedek; Madu, Aleksius; Utomo, Susilo Setyo (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
This community service activity aims to explore the positive impact of using historical site media in an educational context, with a focus on student character development. Training and mentoring are directed at improving teachers' skills in integrating such media into the curriculum, so that students can develop a better understanding of historical values and character. The activity method involves intensive training, mentoring, and evaluation of the impact on the success of the activity with the main target being social studies teachers in junior high schools and senior high schools in Amanuban Central District. The stages of the activity are planning, implementation, evaluation, and reflection. The results obtained show 94.5% of teachers are very satisfied with this training activity and can provide practical guidance for teachers, schools, and related parties to more effectively integrate historical site media as a learning tool that can shape students' positive character